Availability and costs of medicines for the treatment of tuberculosis in Europe. (January 2023) - Günther, Gunar; Guglielmetti, Lorenzo; Leu, Claude; Lange, Christoph; van Leth, Frank; ,; Hasan Hafizi,; Khachatryan, Naira; Aroyan, Harut; Kabasakalyan, Eduard; Knappik, Michael; Skrahina, Alena; et al.
Abstract: Objectives: To evaluate the access to comprehensive diagnostics and novel antituberculosis medicines in European countries. Methods: We investigated the access to genotypic and phenotypic Mycobacterium tuberculosis drug susceptibility testing and the availability of antituberculosis drugs and calculated the cost of drugs and treatment regimens at major tuberculosis treatment centres in countries of the WHO European region where rates of drug-resistant tuberculosis are the highest among all WHO regions. Results were stratified by middle-income and high-income countries. Results: Overall, 43 treatment centres from 43 countries participated in the study. For WHO group A drugs, the frequency of countries with the availability of phenotypic drug susceptibility testing was as follows: (a) 75% (30/40) for levofloxacin, (b) 82% (33/40) for moxifloxacin, (c) 48% (19/40) for bedaquiline, and (d) 72% (29/40) for linezolid. Overall, of the 43 countries, 36 (84%) and 24 (56%) countries had access to bedaquiline and delamanid, respectively, whereas only 6 (14%) countries had access to rifapentine. The treatment of patients with extensively drug-resistant tuberculosis with a regimen including a carbapenem was available only in 17 (40%) of the 43 countries. The median cost of regimens for drug-susceptible tuberculosis, multidrug-resistant/rifampicin-resistant tuberculosis (shorter regimen, including bedaquiline for 6 months), and extensively drug-resistant tuberculosis (including bedaquiline, delamanid, and a carbapenem) were €44 (minimum–maximum, €15–152), €764 (minimum–maximum, €542–15152), and €8709 (minimum–maximum, €7965–11759) in middle-income countries ( n  = 12) and €280 (minimum–maximum, €78–1084), €29765 (minimum–maximum, €11116–40584), and €217591 (minimum–maximum, €82827–320146) in high-income countries ( n  = 29), respectively. Discussion: In countries of the WHO European region, there is a widespread lack of drug susceptibility testing capacity to new and repurposed antituberculosis drugs, lack of access to essential medications in several countries, and a high cost for the treatment of drug-resistant tuberculosis.